Meta Narrative Review of Indonesian Homeschooling in the Digital Era (Equilibrium: Jurnal Pendidikan, 2026)
Homeschooling in Indonesia has developed from a marginal family-based practice into a legally recognized alternative pathway within the national education system. Yet research on its legality, pedagogy, digital mediation, and child development remains dispersed across different disciplines. Objective: This article synthesizes Indonesian homeschooling scholarship through a meta-narrative systematic review to identify the main research traditions, their assumptions, and their implications for policy and practice. Methods: Following RAMESES-oriented principles, literature published between 2014 and 2024 was searched in Google Scholar Indonesia, Garuda, SINTA, and related indexed sources using Indonesian and English keywords. Twelve Indonesia-focused studies were selected and mapped by focus, method, narrative tradition, and key findings. Findings: Three dominant narratives emerged: legal-administrative studies emphasize recognition, equivalence examinations, and PKBM procedures; socio-digital studies highlight ICT-supported autonomous learning and learning hubs; and psychological-developmental studies foreground flexibility, parental roles, agency, and well-being. Conclusion: Homeschooling offers adaptive learning but requires assessment models that protect autonomy while ensuring accountable quality.